Interpreting the Evidence on Wine Consumption and Health: A Narrative Review of the J-Shaped Association and Contemporary Alcohol Guidelines - Creina S. Stockley; Robert Curtis Ellison; Mladen Boban (Nutrients, 2026)
Moderate wine consumption has historically been associated with a J-shaped relationship between dose and total mortality, driven primarily by cardiovascular protection, enhanced endothelial function, improved glucose metabolism, and anti-inflammatory and antioxidant effects attributable to both ethanol and grape-derived phenolic constituents. Yet in recent years, international alcohol guidelines have shifted markedly towards the assertion that ‘no safe level’ of alcohol exists. This transition has occurred despite the continued consistency of mechanistic, clinical, and epidemiological evidence demonstrating hormetic (biphasic) responses to wine and its constituents and despite methodological controversies over the mathematical models used in several recent national guideline revisions. This narrative review synthesises mechanistic evidence on hormesis and wine-specific biological effects—including polyphenols, resveratrol, nitric oxide signalling, platelet modulation, and endothelial benefits—with epidemiological data on J-shaped associations with cardiovascular disease, diabetes, and total mortality. It further examines key methodological changes in recent guidelines, particularly the adoption of the ‘Sheffield model’ and the exclusion of or reduced emphasis on cardioprotective outcomes. The review argues that these methodological decisions, rather than new scientific evidence, largely explain the departure from earlier guideline thresholds that allowed moderate wine consumption. Understanding wine’s biological specificity, the differential health implications of drinking patterns and contexts, and the limitations of model-driven policy changes is essential to develop coherent, evidence-informed public health recommendations.